Métodos para seleção de palavras-chave em sistemas de publicidade contextual - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
In this work we address the problem of selecting keywords for contextual advertising systems in two di erent scenarios: web pages and short texts. We deal with the problem of selecting keywords from web pages using machine learning. While traditional machine learning approaches usually have the goal of selecting keywords considered as good by humans. The new machine learning strategy proposed drives the selection by the expected impact of the keyword in the nal quality of the ad placement system, which we name here as ad collection aware keyword selection (also referred in this work as ACAKS). This new approach relies on the judgement of the users about the ads each keyword can retrieve. Although this strategy requires a higher e ort to build the training set than previous approaches, we believe the gain obtained in recall is worth enough to make the ad collection aware approach a better choice. In experiments we performed with an ad collection and considering features proposed in a previous work, we found that the new ad collection aware approach led to a gain of 62% in recall over the baseline without dropping the precision values. Besides the new alternative to select keywords, we also study the use of features extracted from the ad collection in the task of selecting keywords. We also present three new methods to extract keywords from web pages which require no learning process and use Wikipedia as an external source of information to support the keyword selection. The information used from Wikipedia includes the titles of articles, co-occurrence of keywords and categories associated with each Wikipedia de nition. Experimental results show that our methods are quite competitive solutions for the task of selecting good keywords to represent target web pages, albeit being simple, e ective and time e cient. Besides selecting keywords from web pages we also study methods for selecting keywords from short texts. Short texts have became a very popular way users adopt for publishing content on the web. Every day, millions of users post their thoughts, needs and feelings on the Web through systems, such as social networks like Facebook and Twitter, or spaces for comments on news web sites. Much of these systems' revenue is from contextual advertising systems, thus selecting keywords in this new scenario raise as a new challenge. We propose and study a novel family of methods which uses the connectivity information present on Wikipedia to discover the most related concepts on each short textual unit. We also used the proposed methods as a new set of features on a Machine Learning Framework to boost the quality of the results obtained. We show that this approach presents a good performance and outperforms the best baselines by more than 35%. Finally, we apply the ACAKS approach on short texts and it yielded good results, outperforming a traditional machine learning approach by more than 80% in precision and 80% in recall.
Keywords: Seleção de palavras-chave; Aprendizado de máquina; Publicidade contextualizada; Keyword selection; Contextual advertising; CIÊNCIAS EXATAS E DA TERRA: CIÊNCIA DA COMPUTAÇÃO